2018
DOI: 10.31018/jans.v10i1.1630
|View full text |Cite
|
Sign up to set email alerts
|

Effect of rejuvenation pruning on the growth, productivity and disease incidence in declining trees of pomegranate (Punica granatum L.) cv. Kandhari Kabuli

Abstract: Pruning of fruit trees is an important aspect for the improvement of fruit quality and to minimize the pests and disease attack. Pruning was performed in the month of December in seven year old unpruned trees of Punica granatum cv. Knadhdri Kabuli having many interfering branching and a heavy infestation of bacterial blight orchard. The pruning treatments viz., T 1 : Retention of 15cm fruiting shoot length, T 2 : Retention of 30cm fruiting shoot length, T 3 : Retention of 45cm fruiting shoot length, T 4 : Rete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
0
2
0
1
Order By: Relevance
“…Application of ethylene 0.2 ml l -1 reduced bacterial blight incidence and enhanced fruit yield/quality in pomegranate (Lalithya et al, 2017). Sharma and Singh (2018) also observed that increasing pruning intensity with thinning significantly reduced disease severity on fruit and leaf surface of pomegranate.…”
Section: Resultsmentioning
confidence: 66%
“…Application of ethylene 0.2 ml l -1 reduced bacterial blight incidence and enhanced fruit yield/quality in pomegranate (Lalithya et al, 2017). Sharma and Singh (2018) also observed that increasing pruning intensity with thinning significantly reduced disease severity on fruit and leaf surface of pomegranate.…”
Section: Resultsmentioning
confidence: 66%
“…Chakma (2014) observed that disease incidence and severity significantly affected by different pruning intensity and lowest disease incidence and severity was recorded in higher pruning intensity. Sharma and Singh (2018) also noted that increasing pruning intensity with thinning significantly minimized disease severity on fruit and leaf surface of pomegranate. Among interaction treatments, significantly lower fruit splitting (1.80 and 1.94 kg/plant) were recorded in withholding irrigation during June + pruning and thinning + ethrel 2 ml/l (P 4 C 2 ) treatment as compared higher fruit splitting (2.51 and 3.24 kg/plant) were recorded in withholding irrigation during March without chemicals (P 1 C 0 ) treatment in the years 2017-18 and 2018-19, respectively (Table 3).…”
Section: Methodsmentioning
confidence: 85%
“…Upaya peningkatan produktivitas suatu tanaman juga dapat dilakukan dengan metode pemangkasan (pruning). Pada beberapa penelitian, perlakuan pemangkasan telah mampu meningkatkan produktivitas serta kualitas buah suatu komoditi seperti Vitis vinivera (Abdel-Mohsen, 2013), Punica granatum (Sharma & Singh, 2018), Capsicum annuum (Sukmawati & Numba, 2018) dan Prunus persica (Lesičar et al, 2016). Akan tetapi, informasi mengenai teknik-teknik peningkatan produktivitas buah kayu ules melalui pemangkasan pada tumbuhan kayu ules di bawah kondisi naungan pohon dan terbuka masih sangat terbatas.…”
Section: Pendahuluanunclassified